A educação possível na ação social nossa senhora de Fátima: moral e ética - Barbosa, Núria Ester Campmany Requena (2013)
This project resulted from research conducted under the area the philosophical and educational in Professional School "Ação Social Nossa Senhora de Fátima" which primary serves youth from public schools (located in the southern region of the city of São Paulo) and economically disadvantaged families. In this place, during the school year, students develop attitudes, behaviors and incorporate moral and ethical values, close to those desired and valued by our society and especially by companies. Therefore, the analysis was made of this educational practice, looking for need (s) differential (s) of success, starting with the hypothesis: 1. The subject "Moral Christian" has an influence on the change in way young people act. 2. The consistency between the theoretical speech and practice of teachers and professionals who work in the school encourages the young. To tying to understand how the actions of teachers and professionals who work in school mobilize and / or encourage students to adopt different postures and attitudes was possible to see to appropriation of values, ethic and citizenship. Also the results obtained in interviews with school students indicate that they realize their personal and moral maturity. As the main theoretical framework that supported this project, the authors Severino, Goergen, Streck e Lauand.